Structural Comparison Between MHC Classes I and II; in Evolution, a Class-II-Like Molecule Probably Came First - Wu, Yanan; Zhang, Nianzhi; Hashimoto, Keiichiro; Xia, Chun; Dijkstra, Johannes M. (Frontiers in Immunology, 2021)
Structures of peptide-loaded major histocompatibility complex class I (pMHC-I) and class II (pMHC-II) complexes are similar. However, whereas pMHC-II complexes include similar-sized IIa and IIb chains, pMHC-I complexes include a heavy chain (HC) and a single domain molecule b2-microglobulin (b2-m). Recently, we elucidated several pMHC-I and pMHC-II structures of primitive vertebrate species. In the present study, a comprehensive comparison of pMHC-I and pMHC-II structures helps to understand pMHC structural evolution and supports the earlier proposed—though debated—direction of MHC evolution from class II-type to class I. Extant pMHC-II structures share major functional characteristics with a deduced MHC-II-type homodimer ancestor. Evolutionary establishment of pMHC-I involved important new functions such as (1) increased peptide selectivity by binding the peptides in a closed groove, (2) structural amplification of peptide ligand sequence differences by binding in a non-relaxed fashion, and (3) increased peptide selectivity by syngeneic heterotrimer complex formation between peptide, HC, and b2-m. These new functions were associated with structures that since their establishment in early pMHC-I have been very well conserved, including a shifted and reorganized P1 pocket (aka A pocket), and insertion of a b2-m hydrophobic knob into the peptide binding domain b-sheet floor. A comparison between divergent species indicates better sequence conservation of peptide binding domains among MHC-I than among MHC-II, agreeing with more demanding interactions within pMHC-I complexes. In lungfishes, genes encoding fusions of all MHC-IIa and MHC-IIb extracellular domains were identified, providing an alternative mechanistic hypothesis for a class II-type to class I direction of evolution.